Cavity-enhanced absorption spectroscopy of methane at 1.73 mu m - Barry, H; Corner, L; Hancock, G; Peverall, R; Ritchie, G (2001)
The integrated cavity output spectroscopy technique has been applied to the study of methane near 1.73 μm using a tunable diode laser. We have shown that this simple approach produces accurate high resolution spectra and have achieved a detection sensitivity of 1.8×10-7 cm-1 for mirror reflectivities of 99.84%. © 2001 Elsevier Science B.V.